Effect of inoculation with rihizospheric bacteria in two varieties of wheat Phase II: greenhouse - Bécquer Granados Carlos José; Lazarovits, George; Nielsen, Laura; Quintan, Maribel; Adesina, Modupe; Quigley, Laura; Lalin, Igor; Ibbotson, Christopher (Revista Mexicana de Ciencias Agrícolas, 2018)
The experiment was carried out in a greenhouse so that the inoculation, both simple and combined (with the rhizospheric bacteria- Sinorhizobium and Azospirllium), en two varieties of Wheat. Materials and methodologies were used in accordance with previously prescribed conventional methodologies for this study. The experimental design was completely randomized, with 4 replicas and 10 treatments. A statistical analysis using two-way variance was done. Fertilized treatment was applied with NH4NO3 (150 ppm/kg soil). The content of chlorophyll foliage was evaluated, dry air weight, dry root weight, length of stem, and germination. In the event that differences appeared, it was determined through use of the Duncan Test, and the differences between varieties with t-Student. It is concluded that combined inoculation with the strain A2 (Sinorhizobium meliloti) and the strain N7 (Azospirillum zeae) had the greatest positive inf luence on the chlorophyll content of the plants. On the other hand, there was a great difference between the two varieties of wheat in terms of length of stem, dry air weight, and dry root weight. The results of dry air weight and dry root weight, upon combining the two factors that were studied, highly depended on the varietal characteristics of the plant and on the native population of rhizobacteria. The germination of the plants was not linked to any of the applied factors in the experiment.